Left atrial fibrosis predicts left ventricular ejection fraction response after atrial fibrillation ablation in heart failure patients: the Fibrosis-HF Study. Issue 12 (23rd August 2020) - Kirstein, Bettina; Neudeck, Sebastian; Gaspar, Thomas; Piorkowski, Judith; Wechselberger, Simon; Kronborg, Mads Brix; Zedda, Angela; Hankel, Anastasia; El-Armouche, Ali; Tomala, Jakub; Schmidt, Thomas; Mayer, Julia; et al.
Abstract: Aims: Atrial fibrillation (AF) and heart failure (HF) often coexist. Catheter ablation has been reported to restore left ventricular (LV) function but patients benefit differently. This study investigated the correlation between left atrial (LA) fibrosis extent and LV ejection fraction (LVEF) recovery after AF ablation. Methods and results: In this study, 103 patients [64 years, 69% men, 79% persistent AF, LVEF 33% interquartile range (IQR) (25–38)] undergoing first time AF ablation were investigated. Identification of LA fibrosis and selection of ablation strategy were based on sinus rhythm voltage mapping. Continuous rhythm monitoring was used to assess ablation success. Improvement in post-ablation LVEF was measured as primary study endpoint. An absolute increase in post-ablation LVEF ≥10% was defined as 'Super Response'. Left atrial fibrosis was present in 38% of patients. After ablation LVEF increased by absolute 15% (IQR 6–25) ( P  < 0.001). Left ventricular ejection fraction improvement was higher in patients without LA fibrosis [15% (IQR 10–25) vs. 10% (IQR 0–20), P  < 0.001]. An inverse correlation between LVEF improvement and the extent of LA fibrosis was found ( R 2 = 0.931). In multivariate analysis, the presence of LA fibrosis was the only independent predictor for failing LVEF improvement [odds ratio 7.2 (95% confidence interval 2.2–23.4), P  < 0.001]. Echocardiographic 'Super Response' was observed in 55/64 (86%) patients without and 21/39 (54%) patients with LA fibrosis, respectively ( P  < 0.001). Conclusion: Presence and extent of LA fibrosis predict LVEF response in HF patients undergoing AF ablation. The assessment of LA fibrosis may impact prognostic stratification and clinical management in HF patients with AF. Graphical abstract: